Features of forming ohmic contacts on basis of GaAs - Дмитрієв, Вадим Сергійович (Technology audit and production reserves, 2012)
The model of forming microelectronic composition of Ag-Ge-In/n-GaAs (111), which takes into account the terms of heat treatment and allows to set dependence between the parameters of ohmic contact and modes of heat treatment, is developed.